Deciphering the dynamics of methicillin-resistant Staphylococcus aureus biofilm formation: from molecular signaling to nanotherapeutic advances - Nirmeen Aboelnaga; Salma W. Elsayed; Nehal Adel Abdelsalam; Salma Salem; Nehal A. Saif; Manar Elsayed; Shehab Ayman; Maha Nasr; Mohamed Elhadidy (Cell Communication and Signaling, 2024)
Abstract Methicillin-resistant Staphylococcus aureus (MRSA) represents a global threat, necessitating the development of effective solutions to combat this emerging superbug. In response to selective pressures within healthcare, community, and livestock settings, MRSA has evolved increased biofilm formation as a multifaceted virulence and defensive mechanism, enabling the bacterium to thrive in harsh conditions. This review discusses the molecular mechanisms contributing to biofilm formation across its developmental stages, hence representing a step forward in developing promising strategies for impeding or eradicating biofilms. During staphylococcal biofilm development, cell wall-anchored proteins attach bacterial cells to biotic or abiotic surfaces; extracellular polymeric substances build scaffolds for biofilm formation; the cidABC operon controls cell lysis within the biofilm, and proteases facilitate dispersal. Beside the three main sequential stages of biofilm formation (attachment, maturation, and dispersal), this review unveils two unique developmental stages in the biofilm formation process for MRSA; multiplication and exodus. We also highlighted the quorum sensing as a cell-to-cell communication process, allowing distant bacterial cells to adapt to the conditions surrounding the bacterial biofilm. In S. aureus, the quorum sensing process is mediated by autoinducing peptides (AIPs) as signaling molecules, with the accessory gene regulator system playing a pivotal role in orchestrating the production of AIPs and various virulence factors. Several quorum inhibitors showed promising anti-virulence and antibiofilm effects that vary in type and function according to the targeted molecule. Disrupting the biofilm architecture and eradicating sessile bacterial cells are crucial steps to prevent colonization on other surfaces or organs. In this context, nanoparticles emerge as efficient carriers for delivering antimicrobial and antibiofilm agents throughout the biofilm architecture. Although metal-based nanoparticles have been previously used in combatting biofilms, its non-degradability and toxicity within the human body presents a real challenge. Therefore, organic nanoparticles in conjunction with quorum inhibitors have been proposed as a promising strategy against biofilms. As nanotherapeutics continue to gain recognition as an antibiofilm strategy, the development of more antibiofilm nanotherapeutics could offer a promising solution to combat biofilm-mediated resistance.